Determination of relationship between foreign exchange rate (USD/MYR) and interest rate with the Kuala Lumpur Composite Index (KLCI) performance / Francis Benedict Linjungan - Linjungan, Francis Benedict (2011)
The stock market or equities securities has become an essential market which plays an imperative function to the economy that develops capital formation in sustaining economic growth. Stock market is a listing stock while statistics reflects the composite value of the stock's components. In Malaysia, it is known as the FTSE Bursa Malaysia Kuala Lumpur Composite Index (KLCI) which represents the top selected companies which is used to represent the characteristics of the components in the stocks, in which it has the same commonality such as trading in the same stock market which belong to same industry or having similar market capitalization.